Asas Lex Favor Reo dalam Perkara Korupsi Pengadaan Chromebook Chrome Device Management: Analisis Normatif dan Praktik Peradilan Indonesia - Bangulu, Rifka Amalia (Consensus : Jurnal Ilmu Hukum, 2026)
The revision of Indonesian criminal law from the WvS to the National Criminal Code (KUHP) certainly has several implications for the Indonesian legal world, one of which is the transition process from the old rules to the new rules. This uses a principle that already exists in both the WvS and the National Criminal Code, known as lex favor reo, which states that if there is a change in the rules, the one that benefits the defendant is the one that is applied. This principle is transitional in nature, serving as a bridge between the effectiveness of one criminal law and the newly enacted criminal regulations. This was directly considered by the judge in the Nadiem corruption case involving the procurement of Chromebook Chrome Device Management laptops, which caused the state to suffer financial losses of Rp2.18 trillion. The state losses were detailed as consisting of Rp1.56 trillion for the education digitization program and US$44.05 million, or Rp621. 39 billion, so it is necessary to look at how the principle of lex favor reo is applied in Indonesian criminal law. This study uses normative juridical research by tracing primary and secondary legal materials, which are analyzed descriptively. The results of the study show that the principle of lex favor reo in the WvS and the new Criminal Code has been regulated and has a clear position, and in the Nadim corruption case, the panel of judges will consider the application of this principle, bearing in mind that its application must be relevant to the facts presented in court.